2002
DOI: 10.1093/oep/54.4.669
|View full text |Cite
|
Sign up to set email alerts
|

Sickness, absenteeism, presenteeism, and sick pay

Abstract: The annual cost of absenteeism from the workplace in the UK has been estimated to be over 1% of GDP. The traditional approach to a discussion of absence has been for the firm to passively accept both wages and sick pay and allow workers to choose their absence behaviour. Most empirical research has been based on this approach. However, if absence is costly why should firms pay extra-statutory sick pay? One reason may be the phenomena of presenteeism (ill workers attending work). This may adversely affect produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 19 publications
1
72
0
3
Order By: Relevance
“…Olaverry and Huertas 2012; Chatterji and Tilley 2002). In this case, a negative relationship with the dependent variable in the two models is expected.…”
mentioning
confidence: 88%
“…Olaverry and Huertas 2012; Chatterji and Tilley 2002). In this case, a negative relationship with the dependent variable in the two models is expected.…”
mentioning
confidence: 88%
“…Johns (1997) summarizes numerous studies showing that less liberal sick pay plans result in less absence. The associated expectation is that they could also stimulate presenteeism (Chatterji & Tilley, 2002). Lovell (2004) cites a lack of paid sick leave as a particular stimulus for presenteeism among female workers.…”
Section: Organizational Policies and Presenteeismmentioning
confidence: 99%
“…This is another example of presenteeism. Likewise, Chatterji and Tilley (2002) report that policies implemented by organisations to reduce absenteeism, such as reductions in sick pay, are more likely to increase presenteeism, which in turn, could lead to more illness and lower productivity. A US survey reported that 56% of employers experienced presenteeism because of some perceived problem in their organisation.…”
Section: Presenteeismmentioning
confidence: 99%